Learning Strategies at SMP Muhammadiyah 5 Ngoro during the Covid-19 Pandemic - Faruq Iqbal Maulana (International Consortium of Education and Culture Research Studies, 2021)
The aim of this study was to analyze the implementation effectiveness of the learning from home (BDR) process during the Covid-19 pandemic in of SMP Muhammadiyah 5 Ngoro. This research used mix method. The data collection technique used was a questionnaire given the students once a month. The subjects of this study were the students of SMP Muhammadiyah 5 Ngoro.Based on the results of research conducted by filling out questionnaires, in general, the implementation of learning from home (BDR)students of SMP Muhammadiyah 5 Ngoro run quite effectively with a percentage of 60-79%. The results of the BDR learning implementation questionnaire which had bad effectiveness with the criteria of 48% were in the evaluation process. It is suggested in learning from home (BDR), teachers are required to be able to design learning activities from planning to evaluating in a simpler, more creative and effective way.